KEBIJAKAN POLITIK HINDIA BELANDA TERHADAP PENDIDIKAN ISLAM DI INDONESIA: SEBUAH TINJAUAN HISTORIS - Latifah Rahmi Hasibuan; Zaianal Efendi Hasibuan (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
The Dutch Colonial Government introduced several policies aimed at regulating and overseeing Islamic education, significantly influencing its development and dynamics in Indonesia. This study utilizes a historical approach and document analysis to investigate the educational policies enforced by the Dutch colonial government and their impact on Islamic education. The research findings indicate that the government of the Dutch East Indies sought to manage and restrict Islamic education through various regulations and the establishment of educational institutions aligned with colonial interests. Additionally, the research sheds light on the resistance of Muslims to these policies and their endeavors to preserve and advance Islamic education in Indonesia.